Tumor Microenvironment–Responsive Peptide-Based Supramolecular Drug Delivery System - Zhang, Wenbo; Yu, Lanlan; Ji, Tianjiao; Wang, Chenxuan (Frontiers in Chemistry, 2020)
Physical and biochemical differences between tumor tissues and normal tissues provide promising triggering factors that can be utilized to engineer stimuli-responsive drug delivery platforms for cancer treatment. Rationally designed peptide-based supramolecular architectures can perform structural conversion by responding to the tumor microenvironment and achieve the controlled release of antitumor drugs. This mini-review summaries recent approaches for designing internal triggers-responsive drug delivery platforms using peptide-based materials. Peptide assemblies which exhibit a stimuli-responsive structural conversion upon acidic pH, high temperature, high oxidative potential, and the overexpressed proteins in tumor tissues are emphatically introduced. We also discuss the challenges of current peptide-based supramolecular delivery platforms against cancer.